(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This lecture text examines the mechanisms for improving the personal and tactical effectiveness of command staff and faculty members in Higher Military Educational Institutions (HMEIs). The study analyzes efficient use of service time within the military management system (time management), the causes of time deficiency, preservation of cognitive capital, as well as the application algorithms of the ALP method, ABC analysis, and the Eisenhower Matrix in operational situations. In addition, the paper scientifically and pedagogically substantiates the role of officers’ self-management in high-stress educational and combat environments, strategies for success, and the principles of “Lifelong Learning” within military Acmeology.